Injectable Biocomposites for Bone Healing in Rabbit Femoral Condyle Defects - Liu, Jianheng; Mao, Kezheng; Liu, Zhengsheng; Wang, Xiumei; Cui, Fuzhai; Guo, Wenguang; Mao, Keya; Yang, Shuying (PLOS ONE, 2013)
A novel biomimetic bone scaffold was successfully prepared in this study, which was composed of calcium sulfate hemihydrate (CSH), collagen and nano-hydroxyapatite (nHAC). CSH/nHAC was prepared and observed with scanning electron microscope and rhBMP-2 was introduced into CSH/nHAC. The released protein content from the scaffold was detected using high performance liquid chromatography at predetermined time interval. In vivo bone formation capacity was investigated by means of implanting the scaffolds with rhBMP-2 or without rhBMP-2 respectively into a critical size defect model in the femoral condyle of rabbit. The releasing character of rhBMP-2 was that an initial burst release (37.5%) was observed in the first day, followed by a sustained release and reached 100% at the end of day 20. The CSH/nHAC showed a gradual decrease in degradation with the content of nHAC increase. The results of X-rays, Micro CT and histological observation indicated that more new bone was formed in rhBMP-2 group. The results implied that this new injectable bone scaffold should be very promising for bone repair and has a great potential in bone tissue engineering.